Antioxidant, anti-tyrosinase, and anti-collagenase properties of Elephantopus scaber leaf and root extracts - Anuar, Fatin Nurul Ain; Zamri, Muhammad Aiman Syafiq; Kamaruddin, Sharir Aizat; Syafruddin, Saiful Effendi; Khazali, Ahmad Suhail (Faculty of Applied Sciences, 2025)
Excessive exposure to ultraviolet (UV) radiation is the most common cause of accelerated skin aging. Due to Malaysia’s geographical location near the equator, skin aging has become a growing health concern, leading to an increasing demand for skincare products. However, some over-the-counter skincare products contain hazardous chemicals such as parabens and formaldehyde. As a result, consumers are now switching to natural-based skincare products. Elephantopus scaber (E. scaber), also known as "Tutup Bumi", is a medicinal herb found in Malaysia. Although E. scaber is widely used for various medicinal purposes, its antiaging properties remain largely unexplored. The objective of this study was to determine the antioxidant and anti-skin aging potentials of E. scaber leaf and root extracts. Total phenolic content (TPC), total flavonoid content (TFC), and 2,2-diphenyl-1-picrylhydrazyl (DPPH) assays were conducted to assess the antioxidant properties of E. scaber extracts. The extracts were also tested for tyrosinase and collagenase inhibition to determine their anti-skin aging properties. E. scaber root (ESR) extract showed higher TPC (63.34 ± 0.56 mg GAE/g) and TFC (156.46 ± 7.43 mg QE/g), but lower DPPH radical scavenging activity compared to E. scaber leaf (ESL) extract. The ESR also exhibited stronger tyrosinase and collagenase inhibitory activities. Therefore, E. scaber, particularly the root part, is a promising candidate for the development of novel natural-based antiaging skincare treatments.